Fostering Civic Engagement Through Heroes’ History in MI Grade 5 - Maharani, Okvi; Suharini, Erni; Widiyatmoko, Arif (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2025)
This research aims to describe the role of learning about the historical struggle of heroes in developing civic engagement among 5th grade Elementary Madrasah (MI) students through an inquiry approach that integrates STEM-R (Science, Technology, Engineering, Mathematics, Religion). The method used is qualitative descriptive with data collection through participatory observation, in-depth interviews, and analysis of reflection tasks and Student Work Sheets (LKPD). The results show that the integration of STEM-R into history learning enhances students' understanding of heroes’ struggles and nurtures values such as of courage, sacrifice, mutual assistance, and steadfast faith which are applicable in daily life. Students become more active, creative, and motivated in their learning and demonstrate civic engagement through real-life action. Although differences in comprehension levels remain, this approach significantly contributes to character building The findings imply thst STEM-R and inquiry-and inquiry-based learning not only improve content mastery but also serve as effective frameworks for value education in primary schools. Practically, educator are encouraged to adopt STEM-R strategies to foster civic awareness and student participation beyond the classroom. Further implementation should include personalized support to ensure all learners internalize heroic values meaningfully.Penelitian ini bertujuan untuk mendeskripsikan peran pembelajaran sejarah perjuangan pahlawan dalam mengembangkan civic engagement pada siswa kelas 5 MI melalui pendekatan inkuiri yang mengintegrasikan STEM-R (Science, Technology, Engineering, Mathematics, Religion). Metode yang digunakan adalah kualitatif deskriptif dengan pengumpulan data melalui observasi partisipatif, wawancara mendalam, serta analisis tugas refleksi dan Lembar Kerja Peserta Didik (LKPD). Hasil penelitian menunjukkan bahwa integrasi STEM-R dalam pembelajaran sejarah mampu meningkatkan pemahaman siswa terhadap materi perjuangan pahlawan serta menumbuhkan nilai-nilai keberanian, pengorbanan, gotong royong, dan keteguhan iman yang diaplikasikan dalam kehidupan sehari-hari. Siswa menjadi lebih aktif, kreatif, dan termotivasi dalam mengikuti pembelajaran dan melakukan aksi nyata yang mencerminkan civic engagement. Meskipun terdapat perbedaan tingkat pemahaman di antara siswa, pendekatan ini memberikan kontribusi signifikan dalam membangun karakter dan keterlibatan sosial. Penelitian ini merekomendasikan pengembangan pembelajaran berbasis inkuiri dan STEM-R secara berkelanjutan serta pendekatan personal untuk mendukung semua siswa menginternalisasi nilai-nilai perjuangan pahlawan.